Evaluation of the Potential Association of Platelet Levels, Mean Platelet Volume and Platelet Distribution Width with Acute Appendicitis - Sepas, Hossein Najd (Open Access Maced J Med Sci, 2019)
BACKGROUND: The occurrence and early management of acute appendicitis among children are especially important due to the difficult diagnosis and nonspecific symptoms of the disease. Diagnosis of appendicitis in children is very difficult due to similarity of its symptoms to other diseases, and also its self-limiting nature Platelet indexes such as mean platelet volume (MPV) and platelet distribution width (PDW) have been suggested as a biomarker of inflammation. AIM: Therefore, we examined the association of MPV and PDW with acute appendicitis in children. METHODS: This cross-sectional study was conducted on 464 patients with suspected acute appendicitis under the age of 18 years referred to the specialised hospitals of the ten studied provinces between October 2014 and October 2015. All data obtained regarding patient’s lab tests, i.e. platelet count, MPV and PDW and also radiological studies and surgical reports were gathered in datasheets and analysed to evaluate the potential association of platelet levels, mean platelet volume (MPV) and platelet distribution width (PDW) with acute appendicitis RESULTS: Our results showed that the MPV was significantly higher in acute appendicitis in comparison to perforated appendicitis as well as acute gangrenous appendicitis. PDW was significantly higher in acute appendicitis in comparison to perforated appendicitis and acute gangrenous appendicitis. The current project indicated that PDW < 10.05 had a sensitivity of 35% and specificity of 75%, platelet count < 229500 had a sensitivity of 24% and specificity of 75% and MPV < 8.95 had a sensitivity of 70% and specificity of 71%. CONCLUSION: Our study suggested that platelet indexes such as MPV and PDW could significantly correlate with acute appendicitis in pediatric patients. Hence, we believe that both MPV and PDW could use as a simple and low-cost lab test for diagnosing acute appendicitis. Also, this study revealed that the MPV lower than 8.95 could be a novel index for diagnosing acute appendicitis with sensitivity of 70% and specificity of 71%.